2011
DOI: 10.1007/s10620-011-1653-7
|View full text |Cite
|
Sign up to set email alerts
|

Therapy with the Opioid Antagonist Naltrexone Promotes Mucosal Healing in Active Crohn’s Disease: A Randomized Placebo-Controlled Trial

Abstract: Background Endogenous opioid peptides have been shown to play a role in the development and/or perpetuation of inflammation. We hypothesize that the endogenous opioid system is involved in inflammatory bowel disease, and antagonism of the opioid–opioid receptor will lead to reversal of inflammation. Aims A randomized double-blind placebo-controlled study was designed to test the efficacy and safety of an opioid antagonist for 12 weeks in adults with active Crohn’s disease. Methods Forty subjects with activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 38 publications
0
82
2
2
Order By: Relevance
“…For the assessment of remission using the CDEIS, a score of <3 indicates endoscopic remission, a score of ≥3 indicates active disease, and a decrease in CDEIS by >5 demonstrates response ( 16,(42)(43)(44) (CEBM 2a). Using relative (rather than absolute) changes in SES-CD and CDEIS scores, such as a decrease from baseline of at least 50%, has been shown to have predictive value for clinical outcomes ( 45 ) (CEBM 2b).…”
Section: Endoscopic Targetsmentioning
confidence: 99%
“…For the assessment of remission using the CDEIS, a score of <3 indicates endoscopic remission, a score of ≥3 indicates active disease, and a decrease in CDEIS by >5 demonstrates response ( 16,(42)(43)(44) (CEBM 2a). Using relative (rather than absolute) changes in SES-CD and CDEIS scores, such as a decrease from baseline of at least 50%, has been shown to have predictive value for clinical outcomes ( 45 ) (CEBM 2b).…”
Section: Endoscopic Targetsmentioning
confidence: 99%
“…Although opioid receptors alone do not cause inflammation, there is no doubt that they can stimulate lymphocytes and macrophages as well as cytokines production. Indeed, opioid receptors blockade actually reduces inflammation in chemically induced colitis 13 . In fact, naltrexone, an opioid antagonist, is able to block acute endotoxic shock by inhibiting TNFα production 14 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, imiquimod and resiquimod, as well as the opioid antagonist naltrexone, have been reported to upregulate OGFr and depress cell proliferation. Indeed, clinical trials using OGF alone have shown that treatment with this peptide has a marked antineoplastic effect by extending survival, without toxicity, in patients with pancreatic cancer (24,26), as well as mucosal healing in Crohn's patients with LDN (25,27).…”
Section: Discussionmentioning
confidence: 99%